Factors Associated with Early Complementary Feeding in Infants Before 6 Months of Age - Pitri, Zilfi Yola; Lubis, Kholilah; H, Desri Nova (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2024)
The achievement of exclusive breastfeeding in Bukittinggi City increased by 71.9%, but the results are still below the national target of 80%, which means that there are still many babies who are given complementary foods before the age of 6 months. The purpose of this study was to determine the factors associated with the provision of complementary foods to infants before 6 months of age in Bukittinggi city in 2024. This type of research is analytic in nature with a cross sectional design. the sample in this study was 49 respondents who were taken by saturation, namely all populations were used as research subjects. Chi Square statistical test. The results showed that 36.7% of respondents gave complementary foods to their babies before the age of 6 months. The results of bivariate data analysis obtained a value of p <0.05 for maternal employment status with a value of p = 0.001 and health worker support with a value of p = 0.023, It is concluded that there is a significant relationship between working mothers and health worker support with the provision of complementary foods to infants before the age of 6 months.